Borate Free Cleaners for Aluminum Alloys. (2015) - Donati, Lorenzo; Vincenzi, Federico; Vincenzi, Fabio; Barba, Walter Dalla; Tomesani, L.
Abstract: The paper analyzes four new borate-free aluminum alloys cleaners, designed for the removal of grease, ink or solid soils contaminating the surface of aluminum components before anodizing or painting stages. Different borate-free formulations (2 proposed by Italtecno MG19 NB2, MG19 NB3 and two available on the market) were tested and investigated evaluating the cleaning efficiency compared to formulation actually in use containing borates and also evaluating the impact in term of corrosion or damage of these new formulations on two different aluminium alloys used in aeronautical applications (2024 clad and unclad).